Organic–Inorganic Hybrid Dielectric Layers for Low-Temperature Thin-Film Transistors Applications: Recent Developments and Perspectives - Javier Meza-Arroyo; Rafael Ramírez-Bon (Technologies)
This paper reviews the recent development of organic–inorganic hybrid dielectric materials for application as gate dielectrics in thin-film transistors (TFTs). These hybrid materials consist of the blending of high-k inorganic dielectrics with polymers, and their resulting properties depend on the amount and type of interactions between the organic and inorganic phases. The resulting amorphous networks, characterized by crosslinked organic and inorganic phases, can be tailored for specific applications, including gate dielectrics in TFTs. As dielectric materials, they offer a synergistic combination of high dielectric constants, low leakage currents, and mechanical flexibility, crucial for next-generation flexible electronics. Furthermore, organic–inorganic hybrid materials are easily processed in solution, allowing for low-temperature deposition compatible with flexible substrates. Various configurations of these hybrid gate dielectrics, such as bilayer structures and polymer nanocomposites, are discussed, with an emphasis on their potential to enhance device performance. Despite the significant advancements, challenges remain in optimizing the performance and stability of these hybrid materials. This review summarizes recent progress and highlights the advantages and emerging applications of low-temperature, solution-processed hybrid dielectrics, with a focus on their integration into flexible, stretchable, and wearable electronic devices.